2004
DOI: 10.1136/jnnp.2003.019638
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-leukocyte interaction and platelet activation in migraine: a link to ischemic stroke?

Abstract: Objectives: Migraine has been identified as an independent risk factor for ischemic stroke. Both neurogenic inflammation and platelet activation have been linked to the pathophysiology of migraine. Increased platelet activation results in up-regulation of specific binding to leukocytes which promotes proinflammatory leukocyte secretion and their tethering to endothelium, a mechanism that has been demonstrated in stroke and which could provide a link to migraine. We aimed to determine whether platelet-leukocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 41 publications
1
81
0
5
Order By: Relevance
“…Taken together, it is possible that migraine with visual aura may promote vasospasm, activate platelet aggregation, [24][25][26] and increased concentration of procoagulant factors. [27][28][29][30] Directly or indirectly in the setting of PFO, these vasoactive substances could gain access to coronary artery as well as cerebral vasculature, Table 3 Hazard ratios (95% confidence intervals [CI]) for the association of migraine with visual aura compared to migraine without visual aura and risk of verified ischemic stroke (all types) where they induce visual aura symptoms, and subsequently may result in brain ischemic injury if larger emboli are formed. Our data suggest that migraine without visual aura is not an isolated risk factor for stroke, in our sample, when compared to healthy controls without any headache history; any association identified can be explained by the traditional stroke risk factors (it is also possible that the number of participants with migraine without visual aura is too low, and the study is underpowered to detect an association with stroke).…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, it is possible that migraine with visual aura may promote vasospasm, activate platelet aggregation, [24][25][26] and increased concentration of procoagulant factors. [27][28][29][30] Directly or indirectly in the setting of PFO, these vasoactive substances could gain access to coronary artery as well as cerebral vasculature, Table 3 Hazard ratios (95% confidence intervals [CI]) for the association of migraine with visual aura compared to migraine without visual aura and risk of verified ischemic stroke (all types) where they induce visual aura symptoms, and subsequently may result in brain ischemic injury if larger emboli are formed. Our data suggest that migraine without visual aura is not an isolated risk factor for stroke, in our sample, when compared to healthy controls without any headache history; any association identified can be explained by the traditional stroke risk factors (it is also possible that the number of participants with migraine without visual aura is too low, and the study is underpowered to detect an association with stroke).…”
Section: Resultsmentioning
confidence: 99%
“…Different pathophysiological mechanisms have been postulated like right-to-left shunting of small subclinical emboli and metabolites bypassing the pulmonary system and causing irritation of the trigeminal nerve or an increased platelet activation and aggregation in response to serotonin could possibly trigger migraine and aura (normally serotonin is metabolized in the pulmonary circulation by the lung monoamine oxidase) [11,12]. A 2010 meta-analysis concluded that closing the PFO could cure all the migraine symptoms in 46% of the patients and reduce the symptoms in about 83% of the patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Unsteady profile period 0.758 s Artery outlet 12.8% of Artery inlet Velocity profile Needle (suction) -400 mL/min Needle (injection) 400 mL/min Vein outlet Pressure-outlet Wall Rigid body [19][20][21][22]. 또 한 활성화된 백혈구는 항원반응 발현을 증가시키게 하여 내 피세포에 혈소판의 부착 및 염증작용을 야기하며, 혈전 형성 에 중요한 역할을 한다 [22].…”
Section: Artery Inletunclassified
“…또 한 활성화된 백혈구는 항원반응 발현을 증가시키게 하여 내 피세포에 혈소판의 부착 및 염증작용을 야기하며, 혈전 형성 에 중요한 역할을 한다 [22]. 따라서 정맥측 문합부의 1 Pa 이 하의 영역을 살펴보는 것은 중요하다.…”
Section: Artery Inletunclassified